Pemetaan Penggunaan Ayat-Ayat Al-Qur’an sebagai Sumber Nilai Moderasi Beragama dalam Buku Siswa Akidah Akhlak MI - Hendri Purbo Waseso; Muhtar Sofwan Hidayat; Anggitiyas Sekarinasih (SUHUF, 2022)
The findings of indications of radicalism and intolerance in student textbooks in previous studies became the initial basis for the importance of mapping the use of the verses of the Qur'an in the student book Akidah Akhlak MI. This article aims to ensure that there are values ​​of religious moderation derived from the verses of the Qur'an in the student book Akidah Akhlak MI. The construction of moderate understanding from an early age is needed as an effort to prevent the growth of radical understanding. Through library research and content analysis of the books of Akidah Akhlak MI students in grades I-VI, it was found that first, the mapping of quotations from the Qur'anic verses in the Akidah Akhlak MI student textbooks seen from the function of their use was divided into three, namely the verse used as the main argument. then an explanation is given to strengthen the material, explain the material first and then quote the verses of the Qur'an, and the quotations from the verses of the Qur'an are not accompanied by explanations. Second, the classification of the use of the Qur'anic verses that contain the value of religious moderation is analyzed based on three perspectives, namely from the use of the terms al wasaṭ, al 'adl and al wazn, viewed from the substance of the verse which has a fair, tolerant, and balanced meaning. from indicators of religious moderation (national commitment, tolerance, anti-violence, and accommodating to local culture). Based on these three perspectives, it was found that a total of 18 verse quotes contained in the Akidah Akhlak MI student textbooks for grades I-VI contain the value of religious moderation. These findings prove that the MI Book of Akidah Akhlak does not contain content that is contrary to the principles of religious moderation.